The safety and efficacy of oral immunotherapy compared to epicutaneous immunotherapy in peanut allergen desensitisation amongst the paediatric cohort—a narrative review - Chowdhury, Ehtesam A.; Jadeja, Olivia C. (Frontiers in Allergy, 2025)
Peanut allergies result from a type 1 hypersensitivity reaction, with a prevalence of approximately 1% in children under 5 years of age. The allergens that instigate this reaction are the peanut proteins (Ara h 1–Ara h 8) for which IgE antibodies are specifically produced. Allergen immunotherapy (AIT), despite the uncertainty regarding its mode of action, has been increasingly utilised with the aim of desensitisation against these allergens. AIT encompasses various modes of administration, including epicutaneous immunotherapy (EPIT) and oral immunotherapy (OIT). The review adheres to Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines, with a comprehensive literature search conducted using databases including MEDLINE®, Embase™, PubMed®, and Google Scholar™. Search terms targeted OIT and EPIT in the desensitisation and management of peanut allergy in children, with studies spanning the past 20 years included based on predefined eligibility criteria. The extent of the immunotherapies' efficacy and safety in children is yet to be thoroughly established; however, OIT demonstrated increased desensitisation rates amongst children when compared to EPIT. The long-term efficacy has not been fully established, with sustained unresponsiveness not reported within most studies. Both modes of administration had a high proportion of participants experiencing adverse effects (AEs), with gastrointestinal symptoms more common with OIT and cutaneous reactions with EPIT. Serious AEs were observed less frequently, however, systemic reactions such as anaphylaxis were more apparent with OIT. Future research should focus on peanut EPIT, as the literature was relatively scarce. Furthermore, research studies should assess sustained unresponsiveness to fully gauge the long-term effects of AIT in children.